The Influence of Leadership Style, Service Quality and Work Motivation on Performance of Police Personnel (Study On South Konawe Resort Police Personnel) - Ali, Azis Do; Hajar, Ibnu; Sri Wiyati Mahrani (International Journal of Management and Education in Human Development, 2021)
This study aims to: 1) examine the effect of leadership style on personnel performance, 2) examine the effect of service quality on personnel performance, 3) examine the effect of work motivation on personnel performance, 4) simultaneously examine the influence of leadership style, service quality and work motivation on performance. personnel. The object of this research is the South Konawe Police Resort. The population of the study was the personnel who served in the Konawe Selatan Polres totaling 146 personnel. Determination of the sample using the Slovin formula with a precision of 5 percent thus the research sample amounted to 107 respondents. Collecting research data using questionnaires, research data were analyzed using SPSS Ver. 22 to determine the results of regression analysis of the influence of the independent variable on the dependent variable. The results of the study: 1) leadership style has a positive and significant effect on personnel performance, 2) service quality has a positive and significant effect on personnel performance, 3) work motivation has a positive and significant effect on personnel performance, 4) simultaneously leadership style, service quality and motivation work have a significant effect on personnel performance.